2013
DOI: 10.1200/jco.2012.48.5896
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Antiviral Treatment With Nucleotide/Nucleoside Analogs on Postoperative Prognosis of Hepatitis B Virus–Related Hepatocellular Carcinoma: A Two-Stage Longitudinal Clinical Study

Abstract: Although it might not affect the HCC-promoting potential of Ct-HBx, NA treatment is effective in normalizing liver function, decreasing HBV-HCC recurrence, and improving postoperative survival. This effect should be validated in a multicenter phase III RCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
294
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(309 citation statements)
references
References 38 publications
11
294
2
2
Order By: Relevance
“…Several retrospective studies and a RCT [27,33,35,39] support this idea. However, the other RCT [38] in our review found that NA therapy significantly decreased early HCC recurrence, while it did not report outcomes on late HCC recurrence. NA therapy may inhibit early HCC recurrence, which usually arises due to diffusion of the primary tumor, by reducing high HBV load and HBV mutations, all of which are associated with HCC metastasis and growth [40][41][42] , as well as by inhibiting HBxAg, which promotes HCC invasiveness and metastatic potential [43,44] .…”
Section: Recurrence-free Survivalmentioning
confidence: 55%
See 2 more Smart Citations
“…Several retrospective studies and a RCT [27,33,35,39] support this idea. However, the other RCT [38] in our review found that NA therapy significantly decreased early HCC recurrence, while it did not report outcomes on late HCC recurrence. NA therapy may inhibit early HCC recurrence, which usually arises due to diffusion of the primary tumor, by reducing high HBV load and HBV mutations, all of which are associated with HCC metastasis and growth [40][41][42] , as well as by inhibiting HBxAg, which promotes HCC invasiveness and metastatic potential [43,44] .…”
Section: Recurrence-free Survivalmentioning
confidence: 55%
“…Several retrospective studies [21][22][23][26][27][28][29]33,35] showed that NA treatment did not lead to significantly higher recurrence-free survival than non-NA treatment, while other retrospective studies [24,25,[30][31][32]34,36,37] and the RCTs [38,39] showed that NA therapy was associated with significantly higher recurrence-free survival than non-NA treatment.…”
Section: Recurrence-free Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the therapy fails to provide obvious clinical benefits for reducing early tumor recurrence or improving short-term overall survival (18)(19)(20)(21). This may reflect the fact that the majority of patients in these trials (19,20) were in the early stages of HCC. A longer follow-up of these patients suggested certain clinical benefit.…”
Section: Indications For Nucleos(t)ide Analog (Na) Therapy After Hepamentioning
confidence: 90%
“…The only two randomized trials (19,20) that we identified in literature searches, as well as large cohort studies (18,19,21) examining NA therapy, found that it significantly reduced late HCC recurrence and improved long-term overall survival in patients with HBV-associated HCC following curative hepatectomy. However, the therapy fails to provide obvious clinical benefits for reducing early tumor recurrence or improving short-term overall survival (18)(19)(20)(21). This may reflect the fact that the majority of patients in these trials (19,20) were in the early stages of HCC.…”
Section: Indications For Nucleos(t)ide Analog (Na) Therapy After Hepamentioning
confidence: 99%